Endosonography for mediastinal disease: esophageal ultrasound vs. endobronchial ultrasound - Meena, Nikhil; Bartter, Thaddeus (Endoscopy International Open, 2015)
Background and study aims: One can approach mediastinal pathology via esophageal ultrasound (EUS) and/or endobronchial ultrasound (EBUS). It has been suggested that EUS is better tolerated by patients. If so, EUS might be the procedure of choice when suspect lesions are accessible via EUS. We studied procedural characteristics of EUS with fine needle aspiration (EUS-FNA) and EBUS with transbronchial needle aspiration (EBUS-TBNA) to see how they differed. Patients and methods: Retrospective review of consecutive EBUS and EUS procedures performed on patients over nine months. One hundred fifty-five procedures were analyzed (61 EUS, 73 EBUS, 21 EUS + EBUS). For EUS, EBUS, and EUS + EBUS, 1.4, 2.0 and 2.5 sites (mean) were sampled, respectively. EUS required approximately one-half of the time of EBUS or the combined procedures; 13.1 vs. 24.1 and 26.9 min, respectively (P < 0.0001 for EUS vs. both EBUS and EUS + EBUS). Sedation dosing was statistically lower for EUS and not significantly different between EBUS and the combined approach. EUS also involved lower oxygen requirements and shorter time to discharge. Because fewer mean sites were sampled with EUS than with EBUS or the combined procedure, we performed analysis restricted to procedures that involved sampling of ≤ 2 sites to determine whether approach-related differences in procedure characteristics were preserved. There were 56 such EUS procedures and 52 such EBUS procedures. EUS remained significantly faster and required less patient sedation. Conclusions: EUS involved statistically significant economies of time and sedation. This has implications with respect to safety and productivity. When applicable, EUS is the procedure of choice.